Marine Debris Pollution and Its Impact on the Mangrove Ecosystem (Case Study: Karimunjawa Island and Kemujan Island, Indonesia) - Rafsanjani Fajrin, Erba; Damar, Ario; Taryono (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Coastal areas possess a diverse potential wealth of natural resources that can be developed and utilized by humans, such as fisheries, marine tourism, and transportation. One form of disruption to the balance of coastal and marine ecosystems is the pollution caused by waste. The Karimunjawa Islands face serious challenges related to waste pollution. Therefore, an identification of carried out regarding the composition of polluting waste as well as impacts or disruptions caused by marine waste pollution on the mangrove ecosystem in the coastal areas of Karimunjawa Island and Kemujan Island. Various types of waste were found at the research site, including plastic, metal, glass, rubber, organic, and others. Based on the enteri locations of Karimunjawa Island and Kemujan Island, 370 items of plastic waste and macro-debris amounted to 442, predominantly on Lumbung Beach. The dominant mangrove is Rhizophora sp., which has muddy sandy substrate. From the results of this study, it can be concluded that this waste situation makes the coastal areas of Karimunjawa Island and Kemujan Island vulnerable to environmental pollution problems. The impact on the environment is a decrease in benthic biota density owing to the abundance of waste. The higher the density of waste, the lower the density of benthic species found in the mangrove ecosystemenvironment.